Mechanical and Physical Regulation of Fibroblast–Myofibroblast Transition: From Cellular Mechanoresponse to Tissue Pathology - D'Urso, Mirko; Kurniawan, Nicholas A. (Frontiers in Bioengineering and Biotechnology, 2020)
Fibroblasts are cells present throughout the human body that are primarily responsible for the production and maintenance of the extracellular matrix (ECM) within the tissues. They have the capability to modify the mechanical properties of the ECM within the tissue and transition into myofibroblasts, a cell type that is associated with the development of fibrotic tissue through an acute increase of cell density and protein deposition. This transition from fibroblast to myofibroblast—a well-known cellular hallmark of the pathological state of tissues—and the environmental stimuli that can induce this transition have received a lot of attention, for example in the contexts of asthma and cardiac fibrosis. Recent efforts in understanding how cells sense their physical environment at the micro- and nano-scales have ushered in a new appreciation that the substrates on which the cells adhere provide not only passive influence, but also active stimulus that can affect fibroblast activation. These studies suggest that mechanical interactions at the cell–substrate interface play a key role in regulating this phenotype transition by changing the mechanical and morphological properties of the cells. Here, we briefly summarize the reported chemical and mechanical cues regulating fibroblast phenotype. We then argue that a better understanding of how cells mechanically interact with the substrate (mechanosensing) and how this influences cell behaviors (mechanotransduction) using well-defined platforms that decouple the mechanical stimuli from the chemical ones can provide a powerful tool to control the balance between physiological tissue regeneration and pathological fibrotic response.